Analisis Preferensi Konsumen Terhadap Pembelian Dimsum Uma Yum Cha di Kota Surakarta - Nataya Nirmala Putri; Joko Sutrisno; Mei Tri Sundari (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2023)
The increase in public interest in consuming ready-made foods such as street food culinary and the number of street vendors in the food or beverage sector is quite high in Surakarta City making more diversity of consumer tastes in choosing snacks, one of the street foods is Uma Yum Cha dim sum. It is necessary to know about consumer preferences so that business owners are able to meet consumer expectations to provide satisfaction to consumers. This study aims to determine consumer preferences and what attributes are considered by consumers in purchasing Uma Yum Cha dim sum in Surakarta City. Sampling using purposive sampling method with 100 respondents. The analysis methods used are chi-square analysis and fishbein multiattribute analysis. The results showed that the categories of each attribute of Uma Yum Cha dim sum that became consumer preferences included dim sum with a slightly spicy savory taste, a quantity of 4 pcs, a soft texture, medium dim sum size, and promotion through internet media and the most considered attribute by consumers in purchasing Uma Yum Cha dim sum consecutively are taste, texture, quantity, size, and promotion